Identification α-Amylase Inhibitors of Vernonia amygdalina Leaves Extract Using Metabolite Profiling Combined with Molecular Docking - Norainny Yunitasari; Tri Joko Raharjo; Respati Tri Swasono; Harno Dwi Pranowo (Indonesian Journal of Chemistry, 2022)
Vernonia amygdalina was reported to be used as a therapy for Diabetes Mellitus (DM). One of the mechanisms of therapy DM was to inhibit the action of the α-amylase enzyme. This study aimed to prove the presence of compounds that could inhibit the action of α-amylase. Vernonia amygdalina leaves were macerated with methanol and partitioned into n-hexane, dichloromethane (DCM), and ethyl acetate (EtOAc). Furthermore, they were tested for α-amylase inhibitory activity and analyzed using liquid chromatography-high resolutions mass spectrometry (LC-HRMS). Molecular docking and molecular dynamics simulation (MD simulation) examined unique compounds in the extract with good activity and chromatogram results. The EtOAc extracts showed potential as α-amylase inhibitors indicated by their IC50 values, namely 3.0 μg/mL. There are five unique compounds in the EtOAc extract predicted as 3-[(2Z)-3,7-dimethylocta-2,6-dien-1-yl]-2,4-dihydroxy-6-(2-phenylethyl)benzoic acid (compound 1), 2-hexylpentanedioic acid (compound 2), (2E,4E)-5-[1-hydroxy-2,6-dimethyl-4-oxo-6-({3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl] oxy}methyl)cyclohex-2-en-1-yl]-3-methylpenta-2,4-dienoic acid (compound 3), 3,5,5-trimethyl-4-(3-{[3,4,5-trihydroxy-6-(hydroxymethyl)oxan-1-yl)oxy}butyl)cyclohex-2-en-1-one (compound 4), and 2-{[(6E)-2,10-dihydroxy-2,6,10-trimethyldodeca-6,11-dien-3-yl]oxy}-6-(hydroxymethyl)oxane-3, 4,5-triol (compound 5). The molecular docking analysis showed that compound 3 had better interaction energy (Ei) (-8.59 kcal/mol) and inhibition constant (Ki) values (0.503 μM) than acarbose. These data were supported by MD simulations based on the parameters of RMSD value, the radius of gyration, and protein-ligand interaction energy.